DETERMINANT ESG PERFORMANCE : THE IMPACT OF SHARIA STATUS, FIRM CHARACTERISTICS AND OWNERSHIP STRUCTURE - Lela Hindasah (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This study aims to analyze the factors influencing Environmental, Social, and Governance (ESG) performance among companies listed on the Indonesia Stock Exchange. The sample consists of 447 firm year observations covering the period from 2021 to 2024. The independent variables examined include Sharia status, firm characteristics namely profitability, leverage, and firm size, as well as ownership structure represented by institutional ownership and foreign ownership. The analysis is conducted using multiple linear regression. The results indicate that Sharia status has a positive and significant effect on ESG performance, suggesting that firms complying with Sharia principles tend to demonstrate better ESG practices than non Sharia firms. In addition, profitability, leverage, and firm size are also found to have positive and significant effects on ESG performance. In contrast, institutional ownership and foreign ownership do not show a significant relationship with ESG performance. These findings highlight that firms’ financial characteristics and adherence to Sharia principles play an important role in enhancing ESG performance. Meanwhile, ownership structure does not appear to be a primary determinant in explaining variations in ESG performance among the sampled firms. This study contributes to the growing literature on ESG determinants in emerging markets and provides practical implications for investors and regulators in promoting sustainable business practices in the Indonesian capital market.